PESONA PROTES DALAM KITAB OBAJA: MENGGALI PERAN PEMBERONTAKAN SUCI DALAM MENGHADAPI KETIDAKADILAN - Anon Dwi Saputro (STTII PURWOKERTO, 2023)
This article describes the charm of protest reflected in the Book of Obadiah, focusing on the role of holy rebellion in the face of injustice. In this article, we explore the historical context behind the Book of Obadiah and the events that triggered the holy rebellion. The Book of Obadiah records the Edomites' holy rebellion against the Israelites, in which Edom took advantage of the Israelites' weakness and suffering to enrich themselves. The holy rebellion in the Book of Obadiah symbolizes resistance to oppression and injustice. The method used to explore the text of Obadiah is a thematic approach with attention to contextual, historical and theological analysis. In conclusion, this article emphasizes the importance of understanding and appreciating the messages contained in the Book of Obadiah. The protest charm in the Book of Obadiah reminds us of the importance of fighting for justice, embracing solidarity, and opposing all forms of injustice in modern society. It is the Book of Obadiah that provides a powerful insight into the role of holy rebellion in the face of injustice. The message leads us to stand firm in the truth, be a voice for the unheard, and fight for justice.